Kedudukan Advokat Terhadap Klien Dalam Mendampingi Pemeriksaan Perkara Pidana Di Tingkat Penyidikan - Danialsyah Danialsyah; Dhina Syahfira (Fakultas Hukum universitas Islam Sumatera Utara, 2021)
Abstract The position of an advocate in assisting clients in criminal cases at the investigation level is very urgent because providing legal assistance to suspects is an advocate's obligation to uphold justice and protect human rights, including the rights of perpetrators of criminal acts which are constitutional rights. Advocates play a role at all levels of examination, namely that at the investigative level, advocates have started to provide assistance and follow the course of investigations so that the rights of suspects can be fulfilled and there is no pressure or coercion from the investigators. Providing legal assistance to perpetrators of criminal acts is important in relation to the principle of equality before the law (everyone is the same before the law). This principle demands the right to legal aid, through the provision of legal assistance to the accused / suspected perpetrator of a criminal act. Keywords: Advocates, Clients, Investigators Abstrak Kedudukan advokat dalam mendampingi klien pada perkara pidana di tingkat penyidikan sangatlah urgen karena pemberian bantuan hukum terhadap tersangka merupakan kewajiban Advokat untuk menegakkan keadilan dan perlindungan terhadap hak asasi manusia, termasuk juga hak asasi pelaku tindak pidana yang merupakan hak konstitusional. Advokat memberikan perannya dalam semua tingkat pemeriksaan yakni peran di tingkat penyidikan advokat sudah mulai melakukan pendampingan dan mengikut jalannya penyidikan agar hak-hak tersangka bisa terpenuhi dan tidak ada tekanan maupun paksaan dari penyidik. Pemberian bantuan hukum terhadap pelaku tindak pidana menjadi penting terkait dengan prinsip equality before the law (setiap orang sama dipandang dihadapan hukum) asas ini menuntut adanya hak bantuan hukum, melalui penyediaan bantuan hukum terdakwa/tersangka pelaku tindak pidana. Kata Kunci : Advokat, Klien, Penyidikan